Dynamics of Contemporary Fatwa in the Social Context of Nationality: A Study of the Thought of Sahal Mahfudz and Yusuf Al-Qaradawi - Aliyah, Nur Fatin; Yusuf, Enjang Burhanudin (Hikmah, 2025)
This research aims to examine contemporary Islamic fatwas through the perspective of national social fiqh, using a literature study approach as the main method. The focus of this study specifically highlights the thoughts of KH Sahal Mahfudz and Yusuf al-Qardhawi, two figures who represent an important approach in the renewal of fiqh to be more relevant to today's social and political dynamics. The findings show that fiqh, as a result of ijtihad, is dynamic and is required to continue to adapt to the times, especially in the context of a complex and global nation-state. The concept of social fiqh initiated by KH Sahal Mahfudz underlines the importance of making social conditions the main footing in formulating fatwas, while the idea of fiqh reality from Yusuf al-Qardhawi emphasizes the urgency of harmonization between Islamic texts and social reality to maintain the relevance of Islamic law. Both have a critical view of the fanaticism of the madhhab and both encourage a moderate approach to fiqh based on maqasid al-syari'ah which has ethical and philosophical value. Overall, this study emphasizes the need for a transformation of the fiqh paradigm from a textual-normative approach to a more contextual, solutive, and responsive model of national social fiqh to the challenges of the modern era.